Neurodevelopmental effects of severe hypoglycemia in children with type 1 diabetes: a systematic review - Almutairi, Mohammad N. A. S. F. (Frontiers in Pediatrics, 2026)
BackgroundType 1 diabetes mellitus (T1DM) is one of the most common chronic autoimmune disorders affecting children and adolescents worldwide. It results from the autoimmune destruction of pancreatic β-cells, leading to a complete lack of insulin. The primary treatment involves lifelong insulin therapy, which must be carefully adjusted to maintain stable blood glucose levels and prevent both high and low blood sugar episodes. Severe hypoglycemia (SH) is one of the most critical acute complications of insulin treatment, especially in young patients who may have a limited ability to recognize hypoglycemic symptoms and exhibit who may have limited ability to recognize hypoglycemic symptoms and experience fluctuations in insulin sensitivity due to growth, hormonal changes, and variable metabolic demands. While the immediate effects of severe hypoglycemia, such as seizures and loss of consciousness, are well established, there is growing interest in its potential long-term neurodevelopmental effects. The developing brain is highly active metabolically and relies on glucose, making it particularly susceptible to energy shortages. This susceptibility is heightened during early childhood, a period marked by significant neuronal growth, synaptic pruning, and myelination. As a result, repeated or early episodes of SH may lead to subtle but lasting changes in brain structure and cognitive abilities.ObjectiveThis systematic review aims to thoroughly analyze the existing literature on the neurodevelopmental and cognitive outcomes related to severe hypoglycemia in children with type 1 diabetes. It specifically investigates whether early or recurrent episodes of SH are associated with measurable deficits in intelligence, memory, attention, executive function, or structural brain changes as revealed by neuroimaging studies.MethodsA systematic search was conducted in electronic databases (PubMed, Web of Science, Scopus, and PsycINFO) for studies published between January 2000 and October 2025. The inclusion criteria focused on original research involving pediatric populations (under 18 years) diagnosed with T1DM who had experienced at least one episode of SH and had undergone neurodevelopmental or neuropsychological assessments. Both observational and experimental study designs were considered. Data were extracted using standardized templates, and the methodological quality was evaluated according to PRISMA guidelines.ResultsA total of 20 studies (≈3,800 participants) were included. The literature consistently indicated that recurrent SH—especially in children younger than six years—was associated with impairments in memory, processing speed, and attention. Neuroimaging studies showed evidence of cortical thinning and reduced gray matter volume in the hippocampus among patients with a history of early SH episodes. However, several studies noted that the effect size was modest and could be influenced by factors such as disease duration, overall glycemic variability, and socioeconomic status.LimitationHeterogeneity in study designs, definitions of SH, neuropsychological measures, and confounder adjustment limits causal interpretation.ConclusionThis review indicates that severe hypoglycemia in children with Type 1 diabetes mellitus (T1DM) may lead to subtle but significant long-term impacts on neurocognitive abilities and brain structure. The strongest effects are observed in cases of recurrent or early-onset severe hypoglycemia. To mitigate risks, it is crucial to implement preventive measures such as educating caregivers, utilizing real-time glucose monitoring, and identifying hypoglycemia unawareness early. Future studies should focus on large-scale longitudinal and neuroimaging research to explore causal relationships and discover protective factors.